2020
DOI: 10.3390/recycling5030020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Metals’ Content in Components Mounted on Printed Circuit Boards from End-of-Life Mobile Phones

Abstract: The electronic components mounted on the printed circuit boards (PCBs) of mobile phones represent a resource that is rich in metals, and after separation from the boards, these components could be considered secondary raw materials. The concentrations of the valuable metals are insignificant when compared with those of complete PCBs; however, they could be significantly higher in a fraction formed from the separated components. This study focused on the analysis of Ag, Au, Cu, Nd, Nb, Ni, Pb, Pd, Sn, and Ta in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Metal Leaching from Waste Printed Circuit Boards (WPCBs) Printed circuit boards contain a variety of base metals such as Cu, Fe, Ni, Al, Sn, Pb, Zn and precious metals including Au, Pd, and Ag. The metal composition in PCBs can vary based on the grades (high or low quality); nevertheless, Cu is the element found in a higher concentration ranging from 16 to 38.8% [45]. As per a study carried out by [46], the presence of 24.178% Cu was confirmed by the characterization of PCBs from a mobile phone.…”
Section: Chemical Leachingmentioning
confidence: 82%
“…Metal Leaching from Waste Printed Circuit Boards (WPCBs) Printed circuit boards contain a variety of base metals such as Cu, Fe, Ni, Al, Sn, Pb, Zn and precious metals including Au, Pd, and Ag. The metal composition in PCBs can vary based on the grades (high or low quality); nevertheless, Cu is the element found in a higher concentration ranging from 16 to 38.8% [45]. As per a study carried out by [46], the presence of 24.178% Cu was confirmed by the characterization of PCBs from a mobile phone.…”
Section: Chemical Leachingmentioning
confidence: 82%
“…The following are available online at https://www.mdpi.com/article/ 10.3390/su131810357/s1, Figure S1: Diagram of the dismantling section, or ECs cutter unit, of the WPCBs recycling tool adapted from reference (Fang, Li et al, 2017) and described in the source article as composed of "a frame (1), a driving motor (2), two cutting knives (3), material carrier chain and belt (4,6), an ECs collecting bin (5) with its bin support (8), a knife mounting fixture (7), a dust filter (9) and an exhaust fan (11). ", Figure S2: Water soluble ionic liquid-based reactor pilot (~1000 L) for the disassembly of WPCBs and the recovery of wide range of tin based solder alloys.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Despite the value of the materials it contains (~USD 60 Bn), only 20% of them are currently recycled [2]. Printed circuit boards (PCBs) represent on average 8% of this electronic waste, yet only about 10 out of the 60-plus chemical elements that they contain are routinely recovered and recycled [3][4][5] The recycling of waste printed circuit boards (WPCBs) depends on both an informal sector focused on precious metals recovery using highly polluting approaches, and industrial processes based on the pyrometallurgy of centralized waste, treated in depreciated smelters to make use of the calorific value of the WPCB's 30 wt% epoxy resins [6]. Overall, only ~30 w% of the WPCBs' mass is truly recycled [7].…”
Section: Introductionmentioning
confidence: 99%
“…It constitutes about 20-30% of the weight of a mobile phone (Nnorom and Osibanjo, 2011). Studies by Osibanjo (2011), Hahladakis (2013), Maragkos et al (2013), Ghodrat et al (2018, Adie et al (2019), Intrakamhaeng et al (2019), Gorewoda et al (2020), andLiang et al (2023) showed that the metal content of PWBs varies depending on the type of mobile phone and year of manufacture. Some of the metallic components of a typical PWB of a mobile phone include economic metals (Au, Ag, Cu), toxic metals (Pb, As, Hg, Cd, Se, Cr), non-toxic metals (Fe, Pd, Zn, Ni, Ca, Mn), and non-metals such as Brominated flame retardants (Priya & Hait, 2018).…”
Section: Introductionmentioning
confidence: 99%